Generation of 1D array of focal segments using spirally polarized beam and Complex Phase Filter. (May 2022) - Senthilkumar, M.; Udhayakumar, M.; Lavanya, M.; Mahadevan, G.; Rajesh, K.B.; Jaroszewicz, Z.
Highlights: Simple method to generating 1D array of focal segment using Complex Phase Filter and spirally polarized beam is demonstrated. The method is simple since well optimized single Complex Phase Filter is used. It is avoids the complexity of using 4Pi configuration to achieve the same. Abstract: A new approach for generating and tuning 1D array of sub wavelength scale electric and magnetic spot, hole, flattop and bubble profiled segments using tightly focused spirally polarized beam phase and amplitude modulated with suitable complex phase filter is proposed and investigated numerically using vector diffraction theory. Numerical result shows that by using a well optimized single Complex Phase Filter (CPF), one can generated and tune the geometry of the 1D chain of electric and magnetic field distribution from sub wavelength scale hole to spot and then to a chain of flattop profiled or bubble structure segments by properly tuning the spirallity of incident spirally polarized beam. These focal field distributions may find potential applications in laser direct writing and optical microscopy, as well as multiple-particle trapping, alignment, and acceleration along the optical axis.